Preparing Principals for High-Need Rural Schools: A Central Office Perspective about Collaborative Efforts to Transform School Leadership - Tricia Browne-Ferrigno; Lawrence W. Allen (Journal of Research in Rural Education, 2006)
This article presents district administrators' reflections about (a) the contextual challenges they face in leading a high-need rural school system in Central Appalachia and (b) the change initiatives they implemented to transform the principalship from school management to instructional leadership. After several years of reform efforts, the district superintendent sought external support to deliver intensive professional development to further the district's efforts. A land-grant research university and the rural district partnered to develop the Principals Excellence Program (PEP) and, in turn, submitted a proposal for funding to support training for two cohorts of practicing principals and administrator-certified teachers who aspire to become principals. The article presents perspectives by the district administrators and leadership educators involved in the district-initiated activities to change the culture of administrative practice.